The role of foreign direct investment in growth: Spain, 1964-2013 - Oscar Bajo-Rubio (Global Labor Organization (GLO), 2020)
Foreign direct investment (FDI) has played a major role in the deep process of transformation experienced by the Spanish economy since the first 1960s, which even intensified following the integration with the now European Union (EU) in 1986. In this paper, we analyse the long-run effects of FDI in Spain, by estimating a production function including the foreign capital stock over the period 1964-2013. We find a significant contribution of foreign capital on the accumulated growth of GDP over the period of analysis, which seems however to have been greater during the first years of the period analysed.
Keywords: F21; F43; O40; 330; Economic growth; Foreign direct investment